ORTHODONTIC AND PROSTHETIC REHABILITATION IN AMELOGENSIS IMPERFECTA – CASE REPORT - Paula Jiman; Andreea Simona Pop; Dana Gabriela Festila; Ada Gabriela Delean; Alexandrina Muntean (Romanian Journal of Oral Rehabilitation, 2022)
Aim of the study Amelogenesis imperfecta (AI) is a term that describes a group of inherited conditions that affect the structure and the appearance of dental enamel in both primary and permanent dentition. Material and methods The oral rehabilitation of patients with AI remains a challenge, for the clinician and for the patient, because it requires long-term collaboration. To illustrate the difficulties in treatment of such pathology, we present a clinical case. Results AI associated with crowding, canine inclusion, and severe enamel impairment with associated hyperesthesia, imposed complex orthodontic and prosthetic treatment. Conclusions Long lasting treatment that involves an interdisciplinary team of specialized dentists is required in order to properly manage a condition such as AI.